2018
DOI: 10.1002/prot.25587
|View full text |Cite
|
Sign up to set email alerts
|

A novel bacterial l‐arginine sensor controlling c‐di‐GMP levels in Pseudomonas aeruginosa

Abstract: Nutrients such as amino acids play key roles in shaping the metabolism of microorganisms in natural environments and in host-pathogen interactions. Beyond taking part to cellular metabolism and to protein synthesis, amino acids are also signaling molecules able to influence group behavior in microorganisms, such as biofilm formation. This lifestyle switch involves complex metabolic reprogramming controlled by local variation of the second messenger 3', 5'-cyclic diguanylic acid (c-di-GMP). The intracellular le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 58 publications
(144 reference statements)
6
30
0
3
Order By: Relevance
“…Conservation of the signature sequences on both domains suggested that the DUAL construct could display both the DGC and the PDE catalytic activities. In agreement with our preliminary evidence on P. aeruginosa PAO1-DPA0575 mutant showing cdi-GMP accumulation in the presence of L-Arginine as carbon source [10], we found that: (a) the DUAL protein is able to hydrolyse c-di-GMP into pGpG in vitro ( Fig. 1B); (b) as expected, the PDE activity is a property of the EAL domain, as it is conserved in the EAL-1 and EAL-2 constructs (Fig.…”
Section: Resultssupporting
confidence: 93%
“…Conservation of the signature sequences on both domains suggested that the DUAL construct could display both the DGC and the PDE catalytic activities. In agreement with our preliminary evidence on P. aeruginosa PAO1-DPA0575 mutant showing cdi-GMP accumulation in the presence of L-Arginine as carbon source [10], we found that: (a) the DUAL protein is able to hydrolyse c-di-GMP into pGpG in vitro ( Fig. 1B); (b) as expected, the PDE activity is a property of the EAL domain, as it is conserved in the EAL-1 and EAL-2 constructs (Fig.…”
Section: Resultssupporting
confidence: 93%
“…In P. aeruginosa PAO1, SadC and RoeA, two of the most important DGCs implicated in biofilm formation, are necessary for the l -arginine response 8 . In addition, a multidomain transmembrane protein with PDE activity encoded by locus PA0575 (RmcA) binds l -arginine in its N-terminal domain, and a mutant in this gene shows increased c-di-GMP levels in response to the amino acid 30 . Homologs of SadC or RoeA are missing in P. putida KT2440, but a homolog of RmcA can be found (PP_0386).…”
Section: Discussionmentioning
confidence: 99%
“…We recently characterized the catalytic moiety of RmcA from the P. aeruginosa strain PAO1, a transmembrane GGDEF-EAL containing phosphodiesterase able to recognize L-Arginine in the periplasmic space [ 26 ] and to degrade c-di-GMP [ 5 ]. We demonstrated that the GGDEF domain binds GTP and allosterically controls the phosphodiesterase activity by allowing the EAL domain to bind to c-di-GMP and dimerize [ 5 ].…”
Section: Resultsmentioning
confidence: 99%